Implementation of a Digital TRNG Using Jitter Based Multiple Entropy Source on FPGA - Garipcan, Ali Murat; Erdem, Ebubekir (Soc Microelectronics, Electron Components Materials-Midem, 2019)
In this study, hardware implementation and evaluation of a true random number generator (TRNG) is presented. For the implementation, Field Programmable Gate Array (FPGA) hardware, in which numerical processes based on an algorithmic basis are carried out, was used. In the system, ring oscillators (ROs) with similar structures were used as a noise source, and true randomness was obtained by sampling the jitter signals originating from the oscillators. However, the most critical cryptographic disadvantage of jitter-based TRNGs is the statistical inadequacy of the system. At this point, in contrast to existing designs, entropy sources derived from the subsets of ROs were used in the sampling and post-processing stage. The statistical quality of the system was improved by using true random numbers/inputs obtained from these entropy sources in the sampling and post-processing stage. With sampling and post-processing inputs, the use of complex post-processing techniques that limit the output bit rate of the generator in the system was not required. Thus, a high-performance adaptable TRNG model with reduced hardware resource consumption is obtained. The statistical validation of the TRNG, which was tested in 6 different scenarios for two separate ring oscillator (RO) architectures and three different operating frequencies, was performed with the NIST 800-22 and AIS31 test packages.
Keywords: Jitter; oscillator rings; FPGA; true random number generators; cryptography